Development of E-Worksheets on Reaction Rate Topics - Herdini Herdini; Roza Linda; Rini Rahma Fadila (Jurnal Tadris Kimiya, 2022)
Students need ICT-based teaching to understand chemistry containing abstract and macroscopic concepts. The study aims to develop electronic worksheets using the Adobe Acrobat 11 Pro application. The Plomp model was used to calculate the total percentage of data collected from expert validation sheets and response questionnaires for educators and students. The results showed that the average percentage score obtained by material and media experts was 88.92% and 90.99%, respectively, in the very valid category. The results of the responses of educators and students in the small-scale test obtained an average percentage score of 88.42% and 85.35%, respectively, with very good and very interesting categories. Based on the result, the electronic worksheets developed for the reaction rate material are feasible for the learning process.